Development of a Fringe Printer With 0.35 μm Pixel Pitch - Yamaguchi, Takeshi; Yoshikawa, Hiroshi (Frontiers in Photonics, 2022)
The development of computational devices provide over 100 Giga-pixel computer–generated holograms (CGH) easily. Especially, performance improvement of graphical processing unit makes faster calculation with a normal personal computer. In contrast, output device of CGH is not reported much. Since CGH is fringe pattern, high resolution and fine pixel pitch are required for output device. We have been developing a direct fringe printer, which consists of a laser, an X-Y stage, an SLM and optical parts available on the market. In our previous report, a liquid crystal panel was used for SLM, which has full HD resolution and 7 μm pixel pitch. Since Pixel pitch of the liquid crystal panel is not small enough for CGH, the optical setup works to demagnify pixel pitch of printed fringe pattern. Also, to record high resolution CGH, calculated fringe pattern is splitted and exposed in tiles by the X–Y stage. As a result, we had reported 0.44 μm pixel pitch and over 100 Gpixel CGHs. However, to output more high quality CGH, development of pixel pitch and resolution is very important. In this paper, we have reviewed optical system of fringe printer, and achieved to output 0.35 μm pixel pitch CGH. Also, we have investigated performance of new fringe printer.